Menakar Konstitusionalitas Kebijakan Redistribusi Tanah untuk Lahan Pertanian dalam UU No. 19 Tahun 2013 - Wildan Humaidi (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2018)
Land redistribution is government policy to implement Article 33 Paragraph (3) of the 1945 Constitution, where the people is the holders of authority over the earth, the water and the other natural resources of Indonesia. In fact, the land redistribution in Law No. 19 of 2013 about the Farmers Protection and Empowerment, specifically Article 59 which states